PERAN WORK-LIFE BALANCE MEMEDIASI PENGARUH FLEXIBLE WORKING TERHADAP JOB SATISFACTION PADA PEKERJA INDUSTRI MEDIA DIGITAL - Suryani, Fuji Alda; Nurhasan, Rohimat; Kurniawan, Deri Alan (JURNAL LENTERA BISNIS, 2026)
The fast evolution of technology has driven changes in work patterns, particularly for workers in content-based positions, who must be able to meet content upload targets while remaining creative. The purpose of this research aims to examine the influence of flexible working on job satisfaction, mediated by work-life balance, particularly in the digital media industry. The method used is an quantitative approach through the distribution of questionnaires with purposive sampling of 100 workers in digital media companies in content-based positions, particularly Millennials and Generation Z, using non-probability sampling techniques. The data was analyzed using Partial Least Square-Structural Equation Modeling (PLS-SEM) assisted by SmartPLS 3.0 software. This research proves that there is a positive impact between flexible working and job satisfaction, flexible working and work-life balance, work-life balance and job satisfaction, and work-life balance acts as a mediator between flexible working and job satisfaction. This study concludes that the implementation of flexible working can increase job satisfaction directly or indirectly through the achievement of work-life balance.